Equivalent expert career paths in small- and medium-sized companies – chance to gain and retain good employees or a threat for managers? - Alexander Konz (Journal of Applied Leadership and Management, 2014)
Research questions: Does a manager in a small- and medium-sized company accept an expert on the same hierarchy level or are conflicts the consequences due to her/his power motivation? Methods: Questionnaire across different hierarchy levels in a medium-sized company Results: Managers are aware of the need for experts and claim that both careers are equal but are motivated by power and reputation and for that reason will not accept an expert on the same hierarchy level.
Keywords: 650